2013
DOI: 10.4314/rj.v1i1.4f
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Activity Assessment of Bacterial Strains Isolated from Urine Samples at Butare University Teaching Hospital (Buth) Laboratory.

Abstract: Urinary tract infections (UTI) are common worldwide and affect all sexes and age groups. An estimated 20% or more of the female population suffers from some form of UTIs in their lifetime. Although antibiotics are the first choice of treatment for many urinary tract infections, antibiotic-resistant strains of bacterial species commonly associated with UTIs, are increasing worldwide. The purpose of this study was to determine the pathogen antimicrobial sensitivity trends of bacterial pathogens associated with U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For example a study reporting more than 80% of Proteus isolates ( n = 6) as resistant to imipenem also reported that 80% of them were susceptible to ceftriaxone and 50% were susceptible to vancomycin, a combination that is highly unusual [ 23 ]. There were other unverified reports of highly unusual resistance patterns from some centers, such as penicillin resistant S. pyogenes [ 24 , 25 ] and vancomycin-resistant S. aureus [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example a study reporting more than 80% of Proteus isolates ( n = 6) as resistant to imipenem also reported that 80% of them were susceptible to ceftriaxone and 50% were susceptible to vancomycin, a combination that is highly unusual [ 23 ]. There were other unverified reports of highly unusual resistance patterns from some centers, such as penicillin resistant S. pyogenes [ 24 , 25 ] and vancomycin-resistant S. aureus [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Rwanda, the limited data available on AMR are restricted to studies conducted to estimate levels of AMR among bacterial pathogens causing diseases in humans. The reported percentages of pathogens resistant to cephalosporins, ciprofloxacin, or gentamycin among patients indicate an increasing trend of antimicrobial resistance in hospitals [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. For example, it was shown that the susceptibility of E. coli to gentamycin, colistin, imipenem, piperacillin, and nalidixic acid was decreasing with time [ 21 ].…”
Section: Introductionmentioning
confidence: 99%